Dwangsom: Investigate the Conceptual Basis of Religious Court on Child Custody Rulings - L, Sudirman; Sunuwati, Sunuwati; Fasieh, Muh. Alim (Jurnal Ilmiah Al-Syir'ah, 2023)
This study aims to investigate the philosophical underpinnings of the law regarding the issue of religious court judges' decisions regarding the right to control and care for children. Various Religious Court decisions cannot be obeyed voluntarily by the party controlling the child (the Defendant) because the mother provides the finest care for children under 12. Based on the decision of the party entitled to care for the child (Plaintiff), and according to the survey, several respondents found the decision to be hollow (illusion). It is a normative study with a conceptual approach that is then descriptively and qualitatively analyzed. Initially, the application of Dwangsom in child support cases was psychological pressure on the Defendant to voluntarily carry out the provisions of the decision and psychological protection for the child, according to the results. Despite this, Dwangsom must be provided upon request. Second, a court decision grants a Dwangsom petition, effectively legalizing the practice in cases of religious child-rearing. Thirdly, the Judge's approval of the Plaintiff's request to establish Dwangsom positively affects the renewal of Islamic family law in Indonesia because numerous decisions regarding child support are not made voluntarily.